2017
DOI: 10.1186/s12889-017-4682-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of activity-supportive environment and motorcycle use among urban Taiwanese adults

Abstract: BackgroundAlthough research has shown that numerous perceived environmental factors are supportive of physical activity, little is known about their associations with sedentary transport in motorcycle-oriented countries. This study examined the association between perceptions of Taiwan’s environmental factors and urban adults’ motorcycle use.MethodsCross-sectional data from 1003 Taiwanese adults aged 20–64 years from three urban cities were collected through telephonic surveys in 2015. Data on motorcycle use, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…[ 28 ] It has been shown in various studies that when the environment is more supportive, people are more likely to adopt the desired behavior. [ 29 30 ] The existing laws and regulations in the country on COVID-19 prevention and the relatively conservative attitude of Filipinos may explain the higher preventive behavior observed in the study. In India, one study even mentioned that participants perceived the following government's protocols as an effective way to avoid infection.…”
Section: Discussionmentioning
confidence: 91%
“…[ 28 ] It has been shown in various studies that when the environment is more supportive, people are more likely to adopt the desired behavior. [ 29 30 ] The existing laws and regulations in the country on COVID-19 prevention and the relatively conservative attitude of Filipinos may explain the higher preventive behavior observed in the study. In India, one study even mentioned that participants perceived the following government's protocols as an effective way to avoid infection.…”
Section: Discussionmentioning
confidence: 91%
“…With regard to motorcycle ownership, Lee and Shiaw [35] (1995) developed a constrained diffusion model of motorcycle ownership and established a model with data obtained in Taiwan. Adults who favorably perceive access to public transport and destinations, presence of sidewalks, and safety from crimes at night are less likely to use motorcycles [36]. Oyedepo et al [37] found that the likelihood of owning a motorcycle increases 1.43 times with a unit increase in the number of household members; by contrast, the likelihood of owning a motorcycle decreases by 1.66 times and 2.17 times with unit increases in average monthly income and academic qualification of the household head, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%